Fabrication and qualification of a 3D-printed laboratory-scale sigma blade mixer - Mangalus, Leroi Christian G.
Three-dimensional (3D) printing is a revolutionary technology utilized to fabricate products for specific purposes. The application of 3D printing technology in fabricating a laboratory-scale sigma blade mixer intended for wet powder mixing presents a cost-effective and customizable alternative to conventional manufacturing techniques. The design of the sigma blade mixer was adapted from the design of Santhosh (2015) and commercially available hand mixers in the market, taking into account the requirements of the end-users. The sigma blade was fabricated using acrylonitrile butadiene styrene (ABS)-like resin through stereolithography (SLA) with the Phrozen Mighty Revo due to its durability, high level of detail and accuracy, and high chemical resistance. The remaining 3D-printed components were produced from polyethylene terephthalate glycol (PETG) and polylactic acid (PLA) using fused deposition modeling (FDM) with the Bambulab X1C, selected for their strength, chemical resistance, and non-toxic properties. Equipment qualification was performed based on a failure mode and effects analysis (FMEA) risk assessment and user requirement specifications that outlined the necessary equipment characteristics to meet the demands of laboratory classes. This process was conducted through design qualification, installation qualification, operational qualification, and performance qualification. Specifically, a lactose/starch blend in an 80:20 ratio was blended using 10% cornstarch paste with FD&C Red 40 as the tracer dye to evaluate the performance of the Sigma blade mixer. The wet powder blend was mixed at a fixed speed of 70 rpm for 10 minutes. The wet powder blend was assessed through visual inspection supported by image analysis using ImageJ software. Results of the qualification tests showed that the 3D-printed laboratory-scale sigma blade mixer was capable of producing homogeneous wet powder blends. The design of the sigma blade mixer was appropriate for its intended function, with all components of the equipment being complete. The assembly, connections, facility, and utilities were conducive and appropriately installed for the operation of the equipment. It also performed as intended within the operational range as the mixer can support a minimum and maximum load of 200 g and 350 g, respectively, run in different speed settings (25, 40, 70, and 90 rpm), and operate at the minimum and maximum time of 1 second and 1 hour 40 mins and 39 seconds. Lastly, the equipment is capable of mixing wet powder blends homogeneously based on visual inspection and image analysis. It is recommended to improve the image analysis set-up and to integrate the control box in the sigma blade mixer assembly.